혐기성 소화조 탈수여액의 질산화 과정에서 아질산성 질소 및질산성 질소의 거동에 관한 연구 - 김광수; 안광호; 서규태 (한국수처리학회지, 22(6), 2014)
The recycled water with high NH3-N concentration, which was returned to activated sludge from anaerobic digester, was oxidized under the oxic condition and also were investigated on the behaviors of NO2--N and NO3--N in the biological nitrification process. The nitrification rate of NH3-N depends on alkalinity in water and the consumed alkalinity for nitrification of NH3-N was 6-8 mg CaCO3/mg NH3-N. In nitrification of recycled water conducted with no injection of activated sludge NO3--N not exist but NO2--N was detected to the high concentration of 140 mg/L. It was considered to why high alkalinity in recycled water was acclerated the growth of nitrosomonas but inhibit the growth of nitrobacter, oxidizing NO2--N to NO3--N. Therefore, to decrease NH3-N loading rate for aerobic basin of activated sludge process issued from recycle water of anaerobic digester, the optimal process for removal of NH3-N in recycle water was considered the anammox process using NO2- as electron acceptor. KCI Citation Count: 0